Record of parasitoidism in nests of the primitively social wasp Zethus miniatus Saussure, 1858 (Hymenoptera, Vespidae) - Jacques, Gabriel C.; Ferreira, Wellington D.; Araújo, Lucas C. S.; Santos, Victor L.; Silveira, Luís C. P. (Entomological Communications, 2024)
This note presents two new records of parasitoidism in the nest of the subsocial wasp’ species Zethus (Zethoides) miniatus Saussure, 1858. The nests were collected in two different localities in the Neotropical Savanna - “cerrado” (Minas Gerais State, Brazil). Two species from different insect orders were recorded parasitizing each of the nests. The parasitoid wasp Brachymeria paraguayensis (Brèthes, 1916) (Hymenoptera: Chalcididae); and the bee fly Anthrax oedipus Fabricius, 1805 (Diptera: Bombyliidae). Our note reinforces the importance of new studies describing the biology of vespids, especially in relation to natural enemies and ecological interactions.